Exercise mediates myocardial infarction via non-coding RNAs - Han, Changliang; Zhai, Cuili; Li, Ailing; Ma, Yongzhi; Hallajzadeh, Jamal (Frontiers in Cardiovascular Medicine, 2024)
Myocardial infarction (MI), a widespread cardiovascular issue, mainly occurs due to blood clot formation in the coronary arteries, which reduces blood flow to the heart muscle and leads to cell death. Incorporating exercise into a lifestyle can significantly benefit recovery and reduce the risk of future cardiac events for MI patients. Non-coding RNAs (ncRNAs) play various roles in the effects of exercise on myocardial infarction (MI). ncRNAs regulate gene expression, influence cardiac remodeling, angiogenesis, inflammation, oxidative stress, apoptosis, cardioprotection, and cardiac electrophysiology. The expression of specific ncRNAs is altered by exercise, leading to beneficial changes in heart structure, function, and recovery after MI. These ncRNAs modulate molecular pathways that contribute to improved cardiac health, including reducing inflammation, enhancing angiogenesis, promoting cell survival, and mitigating oxidative stress. Furthermore, they are involved in regulating changes in cardiac remodeling, such as hypertrophy and fibrosis, and can influence the electrical properties of the heart, thereby decreasing the risk of arrhythmias.Knowledge on MI has entered a new phase, with investigations of ncRNAs in physical exercise yielding invaluable insights into the impact of this therapeutic modality. This review compiled research on ncRNAs in MI, with an emphasis on their applicability to physical activity.